THE EFFECT OF PAPAIN ENZYM CONCENTRATION ON PROTEIN HYDROLYSIS OF MUDSKIPPER (Periopthalmus minutus) - Ega Aryanda Putra; Edison Edison; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This study aimed to determine the best concentration of papain enzymes on fish protein hydrolysate, including non-protein nitrogen, proximate chemical composition, yield, and total amino acids. This research was carried out in 3 stages, namely 1) preparation of fish meat, 2) Making of fish flour, 3) Making of fish protein hidrolysate. The results showed that the use of papain enzymes had affected significantly to the characteristics of the protein hydrolysate and the concentration of papain 14% was the best concentration in making the mudskipper protein hydrolysate. The product contain of non-protein nitrogen was 8,2259 mg/l, water was 65.00% (w/w), ash was 8.83% (d/w), fat was 1.67% (d/w), and protein was 80.00% (d/w). Keywords: enzym papain, hydrolysis of protein, mudskipper